KOMPONEN PRODUKSI DAN PRODUKSI PADI PADA PENGGUNAAN PUPUK HAYATI DAN PUPUK ORGANIK CAIR DI SAWAH IRIGASI - Rosmala Widijastuti; Kaimuddin Kaimuddin; Elkawakib Syam’un (Universitas Musamus, Merauke, Papua, 2016)
The combination of organic and anorganic fertilizer treatment can increase rice production. This research aims: (a) to investigate the right compositions of the application of the fertilizing packages which could the best affect the production of paddy crops; (b) to determine the effects the right combination of the N, biological and liquid organic fartilizers on the growth and production of the paddy crops. The methodology used the Split Plot Design (SPD). The results showed that the application of a half dose of urea +2.5 L of Azotobacter + 2.5 L of Azospirillum has given the best and highest number of shoots (10.69 shoots), the highest number of productive shoots (9.52 shoots), the longest panicle (22.10, and the highest number of full grains (84.63 grains/panicle-1). The treatment of the recommendation a half dose of urea + 2.5 L of Azotobacter has given the highest weight of grains (2.67 grams/panicle-1). The best interaction response on the application of the fertilizing packages was packages of 5.0 L of Azotobacter and the application of the liquid organic fertilizers of 6 ccmL-1 which had the lowest empty grains (22.94 grains/panicle-1), and the lowest percentages of empty grains (22.8 grains/panicle-1).